The Dimensions of Primary Mitochondrial Disorders - Schlieben, Lea D.; Prokisch, Holger (Frontiers in Cell and Developmental Biology, 2020)
The concept of a mitochondrial disorder was initially described in 1962, in a patient with altered energy metabolism. Over time, mitochondrial energy metabolism has been discovered to be influenced by a vast number of proteins with a multitude of functional roles. Amongst these, defective oxidative phosphorylation arose as the hallmark of mitochondrial disorders. In the premolecular era, the diagnosis of mitochondrial disease was dependent on biochemical criteria, with inherent limitations such as tissue availability and specificity, preanalytical and analytical artefacts, and secondary effects. With the identification of the first mitochondrial disease-causing mutations, the genetic complexity of mitochondrial disorders began to unravel. Mitochondrial dysfunctions can be caused by pathogenic variants in genes encoded by the mitochondrial DNA or the nuclear DNA, and can display heterogenous phenotypic manifestations. The application of next generation sequencing methodologies in diagnostics is proving to be pivotal in finding the molecular diagnosis and has been instrumental in the discovery of a growing list of novel mitochondrial disease genes. In the molecular era, the diagnosis of a mitochondrial disorder, suspected on clinical grounds, is increasingly based on variant detection and associated statistical support, while invasive biopsies and biochemical assays are conducted to an ever-decreasing extent. At present, there is no uniform biochemical or molecular definition for the designation of a disease as a “mitochondrial disorder”. Such designation is currently dependent on the criteria applied, which may encompass clinical, genetic, biochemical, functional, and/or mitochondrial protein localization criteria. Given this variation, numerous gene lists emerge, ranging from 270 to over 400 proposed mitochondrial disease genes. Herein we provide an overview of the mitochondrial disease associated genes and their accompanying challenges.